Intravenous 64-multi-detector row CT-cholangiography of porcine livers: a feasibility study with definition of the temporal window for optimal bile duct delineation - Sommer, Christof-Matthias; Schwarzwälder, Christoph Bernhard; Ramsauer, S.; Stampfl, Ulrike; Stiller, Wolfram; Nickel, Felix; Omri, Wafa; Kenngott, Hannes Götz; Gehrig, Tobias; Meinzer, Hans-Peter; Kauczor, Hans-Ulrich; Radeleff, Boris (Journal of hepato-biliary pancreatic sciences, 2010)
Background/purpose To assess the feasibility of intravenous 64-multi-detector row computed tomography (CT)-cholangiography of porcine livers with definition of the temporal window for optimal bile duct delineation. Methods Six healthy Landrace pigs, each weighing 28.97 ± 2.99 kg, underwent 64-multi-detector row CT-cholangiography. Each pig was infused with 50 ml of meglumine iotroxate continuously over a period of 20 min and, starting with the initiation of the infusion, 18 consecutive CT scans of the abdomen at 2-min intervals were acquired. All series were evaluated for bile duct visualization scores and maximum bile duct diameters as primary study goals and bile duct attenuation and liver enhancement as secondary study goals. Results Of the 16 analyzed biliary tract segments, maximum bile duct visualization scores ranged between 4.00 ± 0.00 and 2.83 ± 1.47. Time to maximum bile duct visualization scores ranged between 10 and 34 min. Average bile duct visualization scores for the 10- to 34-min interval ranged between 3.99 ± 0.05 and 2.78 ± 0.10. Maximum bile duct diameters ranged between 6.47 ± 1.05 and 2.65 ± 2.23 mm. Time to maximum bile duct diameters ranged between 24 and 34 min. Average bile duct diameters for the 10- to 34-min interval ranged between 6.00 ± 0.38 and 2.40 ± 0.13 mm. Conclusions Intravenous 64-multi-detector row CT-cholangiography of non-diseased porcine liver is feasible, with the best bile duct delineation acquired between 10 and 34 min after initiation of the contrast agent infusion.
Gesehen am 16.08.2023